Small farms: Changing structures and roles in economic development - Joachim von Braun; Alisher Mirzabaev (University of Bonn, Center for Development Research (ZEF), 2015)
Small farms are the largest employment and small business group among the poor. Their businesses use mostly labor and local resources and face local constraints, but at the same time, they are affected by increasingly complex national and global economic changes, which lead to shifts in optimality and viability of structures and of their business priorities. This paper identifies basic forces of change in the small farm economy, proposes policies that may support productive and socially acceptable transformations, and highlights research priorities. The paper concludes that policies should primarily focus on peoples income opportunities in the rural economy, where small farmers often hold multiple farm and non-farm jobs, rather than be narrowly concerned with viability of the small scale farm enterprise.
Keywords: O13; O33; Q01; Q12; 330; small farms; structural change; farm size; sustainability; poverty reduction; innovation